Entropic effects make a more tightly folded conformer of a β-amino acid less stable: UV-UV hole burning and IR dip spectroscopy of l-β3-homotryptophan using a laser desorption supersonic jet technique - Sohn, Woon Yong; Kim, Jeong Jin; Jeon, Myeongwon; Aoki, Takuma; Ishiuchi, Shun Ichi; Fujii, Masaaki; Kang, Hyuk (Physical Chemistry Chemical Physics, 2018)
UV-UV hole burning and IR dip spectra of l-β3-homotryptophan were measured by a laser desorption supersonic jet technique as a bottom-up approach to understand the secondary structures of β-peptides. 14 conformers were found by UV-UV hole burning spectroscopy. The conformers were classified into three groups depending on their hydrogen bonding patterns observed in their conformer-specific IR spectra, and tentatively assigned by comparing with quantum chemical calculations. Group 1 had free OH stretch but no NH2 anti-symmetric stretch vibrational transition and was assigned to NH-π hydrogen bonded structures. Group 2, including the most abundant conformer, showed both free OH and NH2 anti-symmetric stretch vibrations, and belonged to NH-O hydrogen bonded conformations. Group 3 of conformers had hydrogen-bonded OH stretch IR transition and had OH-N hydrogen bonds. The internal hydrogen bond of group 3 is a C6 hydrogen bond due to the additional carbon atom at the β position and shows a shorter bond length than that of a C5 hydrogen bond. While the OH-N C6 hydrogen bond is stronger than NH-O, the entropic effect prefers the more flexible NH-O hydrogen bonded structure. It is expected that the unnatural C6 hydrogen bond influences the conformations of β-peptides and builds totally different secondary structures than those of α-peptides.
Keywords: Entropy; Hydrogen Bonding; Models, Molecular; Molecular Conformation; Quantum Theory; Spectrophotometry, Infrared; Tryptophan